HUBUNGAN PENGGUNAAN MULTIMEDIA TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS VA SD NEGERI 37 PEKANBARU - Nur, Zullayli; Ain, Siti Quratul (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
In the context of elementary school education, students' interest in science subjects is often less than optimal due to the perception of difficulty and the abstract nature of the material. This study aims to determine the relationship between the use of multimedia and students' interest in science education at the elementary school level. This study uses a quantitative approach method. The quantitative approach is also called a positivist approach because it is based on the philosophy of positivism. Research is conducted to compare the similarities and differences between two or more facts based on a certain framework of thought. to find out how one treatment with controlled conditions correlates with another. The data technique used in this study is the "product moment" correlation statistical analysis technique to analyze the relationship between the use of multimedia in the teaching and learning process in the field of science. Based on the results and discussion of the findings, it can be concluded that the use of multimedia in Natural Science learning in class V of SD Negeri 37 Pekanbaru has a significant positive influence on students' learning interest, so that it can increase the effectiveness of the learning process. This can be seen in the Fhiting value = 109398.203 with a significance level of 0.000 <0.05, then the regression model can be used to predict the participation variable or in other words there is an influence of the multimedia variable (X) on the learning interest variable (Y). Keywords: Multimedia; Learning Media; Correlations